Teori Naskh dalam Pandangan William Montgomery Watt dan Richard Bell (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
This article discusses about two figures’ thought, William Montgomery Watt and Richard Bell, about the Qur’an, especially about naskh or an-nasikh wa-l-mansukh in the Qur’an. The discussion about the theory of naskh evidently results different proclivity of the thoughts. Watt which in one hand accepted the truth of the revelation of Muhammad and in another hand perceived the alteration of revelation in sociological perspective, also proposed hypotheses in which the alteration of revelation might be the result of Prophet’s addition, although he said that his hypotheses had not have a strong proof. Meanwhile, Bell saw that naskh tends to Prophet’s revision on compilizing the verses within the Qur’anic chapters though he also mentioned naskh in understanding of that the abrogation of the law of verse which being remained in the Qur’an. This article is based on descriptive-analitical and comparative methods.